Public parts, resocialized autonomous communal life. (December 2021) - Rodrigues Silva Dória, David; Ramaswami, Keshav; Claypool, Mollie; Retsin, Gilles
Commoning embodies the product of social contracts and behaviors between groups of individuals. In the case of social housing and the establishment of physical domains for life, commoning is an intersection of these contracts and the restrictions and policies that prohibit and allow them to occur within municipalities. Via a platform-based project entitled Public Parts (2020), this article will also present positions on the reification of the common through a set of design methodologies and implementations of automation. This platform seeks to subvert typical platform models to decrease ownership, increase access, and produce a new form of communal autonomous life amongst individuals that constitute the rapidly expanding freelance, work from home, and gig economies. Furthermore, this text investigates the consequences of merging domestic space with artificial intelligence by implementing machine learning to reconfigure spaces and program. The problems that arise from the deployment of machine learning algorithms involve issues of collection, usage, and ownership of data. Through the physical design of space, and a central AI which manages the platform and the automated management of space, the core objective of Public Parts is to reify the common through architecture and collectively owned data.